A method for preparing a 3D-printed carbon nanotube reinforced waste slag-based inorganic polymer
Patent Information
- Application Number
- CN202311807811.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-12-26
AI Technical Summary
[0012]本发明针对传统无机聚合物成型方法单一、力学性能需要改良、不能适用于各种建筑场景、功能单一、应用有限的问题,传统的无机聚合物吸附材料没有较好的力学性能的问题,以及煤矸石、粉煤灰、偏高岭土和矿渣等工业废渣的再次利用、高附加值利用问题,提供了一种3D打印的碳纳米管强化废渣基无机聚合物的制备方法,使用多种工业固废为原材料,得到可用于3D打印直写成型技术的浆料配比,并在浆料中加入碳纳米管以增强其力学性能,在浆料中加入发泡剂以增大其比较面积进而强化其吸附性能,最后将提前设计好的3D模型打印出实物产品,利用3D陶瓷打印机打印出提前在计算机软件中设计的3D模型,实现复杂结构的无机聚合物制备的智能化
[0033]与已有技术相比,本发明的有益效果为:本发明制备得到的碳纳米管强化无机聚合物,碳纳米管、H2O2的协同作用使制备的材料的力学性能和吸附性能都相对优良,制备的过程中使用水浴降温法使浆料保持较长时间的可挤出状态,借助3D打印直写成型工艺,短时间、高效率的获得了碳纳米管强化无机聚合物。本发明获得的无机聚合物有潜力作为新型的功能材料,废渣也被有效再次利用,达到了环保节能的效果;处理工艺简单,成型快速,用药量少,处理效果良好,性能稳定,力学性能得到了提高,也有较好的吸附性能,具有很好的经济效益和广泛的社会效益。
Smart Images

Figure CN117776606B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of intelligent and green manufacturing technologies, and in particular to a method for preparing 3D-printed carbon nanotube-reinforced waste-based inorganic polymers. Background Technology
[0002] With the continuous development of the construction industry, the requirements for various performance aspects of buildings are becoming increasingly higher, while labor costs are also becoming increasingly expensive. It is urgent to seek better building materials and faster, more efficient automated construction processes.
[0003] Industrial production inevitably generates pollutants such as wastewater, waste residue, and waste products. Large-scale industries, particularly metallurgy, manufacturing, agriculture, nuclear power, and paper and printing, which bear a heavy burden on the national economy, are also major sources of industrial pollution. These pollutants have a significant impact on the ecological environment, residents' lives, and sustainable social development. Therefore, addressing the issues of reducing, effectively controlling, and reusing industrial waste is urgently needed.
[0004] Solid waste treatment, one of the "three wastes," is a challenging and significant issue. There are many methods for solid waste treatment, involving physical, chemical, and biological control methods. One popular and environmentally friendly method is to use solid waste as a basis to prepare inorganic polymers, thereby achieving the reuse of solid waste.
[0005] Wastewater treatment, one of the "three wastes" (wastewater, waste gas, and solid waste), is a major issue in the environmental protection field. Traditional wastewater is directly discharged into rivers or oceans, which greatly affects the ecological environment and water safety. There are many wastewater treatment methods, including biological, physical, and chemical methods. Among them, adsorption is a practical and relatively low-cost physical method, while inorganic polymer adsorption is also a popular method nowadays.
[0006] However, traditional inorganic polymer material molding processes are simplistic, often employing direct casting and demolding methods. This results in inorganic polymers with fixed sizes and shapes, significantly limiting their application. The emergence of 3D printing technology effectively solves this problem. Using computer software capable of creating 3D models, diverse 3D models of varying sizes and shapes can be designed. These models are then printed using an extrusion 3D printer, enabling the application of inorganic polymers in various fields such as construction, machinery, and wastewater adsorption. This provides a new solution and significant impetus for the effective treatment of industrial waste.
[0007] Currently, materials commonly used for extrusion 3D printing at home and abroad include: cement, concrete, ceramic materials such as Al2O3 and SiC, polymer materials such as resin, aluminosilicate polymers, agricultural waste, and metal composite materials. Among them, 3D printing of cement has been extensively studied and widely used, but it requires large equipment, has high costs, and is prone to clogging during the printing process. The study, titled "Zhao Ying, Liu Weisheng, Wang Huan, et al. Effect of limestone powder on the properties of 3D printed cement-based materials [J]. Materials Reports, 2021, 34(Z2): 217-220," focuses on silicate cement-based materials incorporating limestone powder. Using 5%-20% limestone powder to replace cement, the study investigates the effects of limestone powder on the workability and mechanical properties of 3D printed cement-based materials. The results show that when the limestone powder content is no more than 10%, the compressive strength of the 3D printed cement-based material is slightly lower than the control sample (3-day compressive strength approximately 11.3 MPa). However, the limestone content significantly affects various printing parameters, and the preparation process is difficult to control the printable time, without achieving value-added utilization of solid waste materials. The paper "Soltan DG, Li VC. A self-reinforced cementitious composite for building-scale 3D printing[J]. Cement and ConcreteComposites, 2018, 90: 1-13" introduces a design for a self-reinforced cementitious composite material for building-scale 3D printing. This design is based on an engineered cementitious composite material containing dispersed short polymer fibers to produce strong tensile strain hardening. This printable ECC material exhibits a tensile strain capacity of approximately 4.0% and a tensile strength close to 6 MPa. The compressive strength of this composition can be rapidly obtained, reaching 30 MPa within 6 days. However, the process is relatively complex and costly, the printed product has slightly inferior molding quality, and it does not achieve value-added utilization of solid waste materials.
[0008] Among the existing published patents, CN110330278A discloses a method for 3D printing graphene oxide-reinforced aluminosilicate polymers. The prepared materials have excellent mechanical properties, but the steps are relatively complex, the cost is high, and the dense material results in low adsorption performance.
[0009] CN113754359A discloses a solid waste fiber-reinforced polymer composite material suitable for 3D printing technology. The method is simple and makes effective use of solid waste materials. However, the types of solid waste raw materials used are not extensive, the adaptability is not high, and the application scope is limited to building materials. The possibility of applying it to adsorb wastewater is not considered. The material is dense, resulting in low adsorption performance. No effective measures to extend the printable time are used in the preparation of the slurry. The time from the completion of slurry preparation to the solidification of the slurry is short, which affects the preparation efficiency and the breadth of application.
[0010] CN116177959A discloses a method for preparing carbonized 3D printed foamed concrete. The preparation method is simple and the material has a porous structure, but the mechanical properties are not very good, the compressive strength is low, and it is not considered for application in the field of wastewater adsorption.
[0011] CN115999515A discloses a method for preparing a biochar-based hierarchical porous monolithic adsorbent, which effectively utilizes biomass solid waste materials and has certain adsorption performance for dyes. However, the biomass materials used have low mechanical properties and are not suitable for large-scale adsorption devices that require mechanical properties. Summary of the Invention
[0012] This invention addresses the problems of traditional inorganic polymer molding methods, such as limited functionality, need for improved mechanical properties, inapplicability to various construction scenarios, single function, and limited applications. It also addresses the lack of good mechanical properties in traditional inorganic polymer adsorbents and the need for reuse and high-value-added utilization of industrial waste such as coal gangue, fly ash, metakaolin, and slag. The invention provides a method for preparing carbon nanotube-reinforced waste-based inorganic polymers for 3D printing. Using various industrial solid wastes as raw materials, a slurry formulation suitable for 3D printing direct-write molding technology is obtained. Carbon nanotubes are added to the slurry to enhance its mechanical properties, and a foaming agent is added to increase its surface area, thereby strengthening its adsorption performance. Finally, a pre-designed 3D model is printed to produce a physical product. A 3D ceramic printer is used to print the 3D model designed in computer software, realizing the intelligent preparation of inorganic polymers with complex structures. By utilizing the reaction and adsorption properties of materials such as slag, fly ash, metakaolin, or coal gangue with alkaline solutions, and through the in-situ introduction of carbon nanotubes during the synthesis process and their mixing under ultrasonication, a novel molding and preparation method is provided to address the problems mentioned in the background art, enabling the secondary high-value utilization of industrial solid waste. The main materials used in this invention are derived from industrial solid waste, resulting in low costs. The reinforcing effect of carbon nanotubes endows the prepared material with good mechanical properties, and the use of H2O2 as a foaming agent gives the material a porous structure, making it applicable to wastewater adsorption. The synergistic effect of carbon nanotubes and H2O2 results in relatively excellent mechanical and adsorption properties of the prepared material. The water bath cooling method used during preparation keeps the slurry in an extrudable state for a longer period, while the novel 3D printing method greatly expands the application scenarios of this invention.
[0013] The technical solution of this invention is as follows: A method for preparing 3D-printed carbon nanotube-reinforced waste residue-based inorganic polymers, comprising the following steps:
[0014] Step 1: Preparation of alkaline activated silicate solution: Potassium silicate solution is mixed with solid potassium hydroxide, with a SiO2:KOH molar ratio of (0.8-1):1. The mixed solution is stirred for 20-600 minutes to obtain an alkaline activated silicate solution; wherein the modulus of potassium silicate solution is 3.1, n(SiO2) / n(K2O)=3.1, and SiO2 accounts for 40% of the mass fraction of potassium silicate solution;
[0015] Step 2: Pre-treatment of inorganic polymer powder mixing: The waste residue consists of two or more of the following: slag, fly ash, metakaolin, and coal gangue; the waste residue is ground separately by mechanical crushing, and the ground waste residue powder is dried and sieved; the sieved waste residue is mechanically mixed according to a certain mass ratio to obtain inorganic polymer powder.
[0016] Step 3: Preparation of alkaline activation solution containing carbon nanotubes: Add carbon nanotubes to the alkaline activation silicate solution, with the mass of carbon nanotubes accounting for 2.5%-35% of the mass of the alkaline activation silicate solution, to obtain an alkaline activation solution containing carbon nanotubes; after ultrasonic dispersion treatment, a well dispersed alkaline activation solution containing carbon nanotubes is obtained.
[0017] Step 4: Preparation of carbon nanotube / inorganic polymer slurry: Add inorganic polymer powder to the carbon nanotube alkaline activation solution, with a mass ratio of inorganic polymer powder to carbon nanotube alkaline activation solution of (120-180):(75-95). Then add deionized water to adjust the viscosity to obtain carbon nanotube / inorganic polymer slurry; wherein the mass ratio of deionized water to carbon nanotube alkaline activation solution is (1-2):(7.5-9.5).
[0018] Step 5: Cooling and mechanical stirring: Cool the container containing the carbon nanotube / inorganic polymer slurry to 0-24℃ and stir the carbon nanotube / inorganic polymer slurry for 15-60 minutes to obtain the carbon nanotube / inorganic polymer composite slurry.
[0019] Step 6: Preparation of foamed printing paste: Add foaming agent H2O2 and thickener CMC to carbon nanotube / inorganic polymer composite paste in sequence. The mass ratio of H2O2 to inorganic polymer powder in step 4 is (0-8):100, and the mass ratio of CMC to inorganic polymer powder in step 4 is (1-25):100. Stir for 3-10 minutes to obtain foamed printing paste.
[0020] Step 7, Printing Slurry Filling and Printing: Transfer the foamed printing slurry into the printing barrel, allowing the slurry in the printing barrel to completely sink to the bottom of the printing barrel for printing, to obtain 3D printed carbon nanotube reinforced inorganic polymer;
[0021] Step 8: Curing of carbon nanotube-reinforced inorganic polymer: Place the obtained 3D-printed carbon nanotube-reinforced inorganic polymer in an oven at 25-80℃ and dry for 0.5-3 days to obtain the final product of 3D-printed carbon nanotube-reinforced inorganic polymer.
[0022] In step two, when two types of waste residue are selected as raw materials, the mass ratio of coal gangue to slag is 1:(0.4-1.2), the mass ratio of coal gangue to fly ash is 1:(0.5-1), the mass ratio of coal gangue to metakaolin is 1:(0.4-0.8), the mass ratio of fly ash to slag is 1:(0.4-1.2), the mass ratio of metakaolin to slag is 1:(0.5-1.8), the mass ratio of metakaolin to fly ash is 1:(0.8-1.5), and the mass ratio of the total mass of inorganic polymer powder to the mass of alkali-activated silicate solution is (1.25-2.5):1; when three types of waste residue are selected as raw materials, the mass ratio of coal gangue:fly ash:slag is 1:(0.5-1):(0.4-1.2), the mass ratio of coal gangue:fly ash:slag is 1:(0.5-1):(0.4-1.2), and the mass ratio of coal gangue to fly ash is 1:(0.8-1.5). The mass ratio of fly ash to metakaolin is 1:(0.5-1):(0.4-0.8), the mass ratio of fly ash to metakaolin to slag is (0.5-1):(0.4-0.8):(0.4-1.2), the mass ratio of coal gangue to metakaolin to slag is 1:(0.4-0.8):(0.4-1.2), and the mass ratio of the total mass of inorganic polymer powder to alkali-activated silicate solution is (1.25-2.5):1. When four types of waste residues are selected as raw materials, the mass ratio of coal gangue to fly ash to metakaolin to slag is 1:(0.5-1):(0.4-0.8):(0.4-1.2), and the mass ratio of the total mass of inorganic polymer powder to alkali-activated silicate solution is (1.25-2.5):1.
[0023] In step three, the mass of carbon nanotubes accounts for 6%-25% of the mass of the alkaline-activated silicate solution.
[0024] In step four, carbon nanotubes account for (5-20):100 of the mass of inorganic polymer powder; the mass ratio of deionized water to carbon nanotube-containing alkaline activation solution is (1-2):(8-8.5).
[0025] In step five, the container containing the carbon nanotube / inorganic polymer slurry is cooled in an environment of 20℃-22℃.
[0026] In step six, the mass ratio of H2O2 to inorganic polymer powder in step four is (2-3):100, and the mass ratio of CMC to inorganic polymer powder is (4-8):100.
[0027] The printing process in step seven is as follows: Under room temperature conditions, the printing cylinder is fixed onto the ceramic 3D printer. The length of the direct-write printing needle is 0.5mm-10mm, the extrusion ratio is 0.5-0.9, the extrusion linewidth is 0.5mm-10mm, the material leakage retraction distance is 0.5mm-1.0mm, the retraction speed is 800mm / s-1800mm / s, the set layer height is 0.5mm-1.0mm, the first layer height is 50%-90% of the set layer height, the first layer extrusion linewidth is 100%, the first layer printing deceleration ratio is 0.3-0.5, the infill rate is 20-50%, the overlap rate between the printed shell and the infill is 10%-20%, the infill extrusion linewidth is 80%-100%, the minimum infill length is 1mm-5mm, and infill is performed once for each printed layer; the air pressure for pneumatic printing is adjusted to 0.05-0.8MPa.
[0028] The main components of the coal gangue are: 50-65 wt% SiO2 and 20-30 wt% Al2O3; the main components of the slag are: 25-35 wt% SiO2, 10-20 wt% Al2O3 and 40-50 wt% CaO; the main components of the fly ash are: 45-55 wt% SiO2, 30-40 wt% Al2O3, 5-10 wt% Fe2O3 and 2-5 wt% CaO; and the main components of the metakaolin are: 48-58 wt% SiO2 and 40-50 wt% Al2O3.
[0029] Inorganic polymers are high-performance materials that can be prepared using industrial solid waste. They consist of a microscopic framework of elements such as Si, O, and Al linked by covalent bonds, extending into a three-dimensional oxide network structure. The preparation of inorganic polymers is simple, requiring only the presence of aluminosilicates in the raw materials, and can be completed under the action of an alkaline activator.
[0030] Traditional inorganic polymer materials, as future building materials, have certain requirements for mechanical properties. Therefore, this invention introduces carbon nanotubes (CNTs) to enhance their mechanical properties. Carbon nanotubes are tubular graphite crystals with a size reaching the nanometer scale. They are seamless nanoscale tubes formed by rolling single or multiple layers of graphite sheets around a central axis at a certain helical angle. Carbon nanotubes have powerful functions and outstanding advantages, including high toughness, high specific surface area, electrical conductivity, high porosity, and high hydrophobicity. They have a wide variety of applications, and are often used as reinforcing agents in the materials field. The addition of appropriate amounts of carbon nanotubes is quite effective in the functional modification of inorganic polymer materials. By using appropriate mixing methods to uniformly disperse carbon nanotubes in the inorganic polymer slurry, a second phase is formed, thereby improving the mechanical properties of the material.
[0031] Another important application of inorganic polymers is as adsorbent materials. Traditional inorganic polymer adsorbents are mostly in the form of powders, microspheres, or fragments, adsorbing harmful substances in dye and heavy metal wastewater onto their surfaces through physical adsorption, chemical adsorption, and electrostatic interactions to reduce or completely remove these harmful substances. These adsorbents often contain special functional groups (such as -OH) and have high specific surface areas. However, these traditional adsorbent materials lack good mechanical properties, are unsuitable for dynamic adsorption, and are difficult to fabricate into independent large-scale adsorption devices. These problems can be solved by using a foaming agent to foam inorganic polymer slurry and then extruding it into complex structures using an extrusion 3D printer.
[0032] By utilizing alkali activation, carbon nanotubes are added to an alkali-activated silicate solution and ultrasonically enhanced for fusion. Industrial solid wastes such as coal gangue, slag, fly ash, and metakaolin are used as raw materials, which are then solidified in the alkali-activated silicate solution. A certain amount of foaming agent and stabilizer are added to prepare a porous slurry reinforced with carbon nanotubes, suitable for 3D printing. A pre-designed 3D model is then printed layer by layer using a 3D printer. This method achieves intelligent material forming. The resulting carbon nanotube-reinforced inorganic polymer possesses excellent mechanical and adsorption properties. Furthermore, the diversity of 3D models allows for a wide range of applications, meeting the needs of various building designs and wastewater adsorption solutions. This provides new ideas for innovation in my country's construction and environmental protection industries, as well as for functional materials containing carbon nanotubes.
[0033] Compared with existing technologies, the beneficial effects of this invention are as follows: The carbon nanotube-reinforced inorganic polymer prepared by this invention exhibits superior mechanical and adsorption properties due to the synergistic effect of carbon nanotubes and H2O2. During the preparation process, a water bath cooling method is used to maintain the slurry in an extrudable state for a relatively long time. Utilizing 3D printing direct-write molding technology, the carbon nanotube-reinforced inorganic polymer is obtained quickly and efficiently. The inorganic polymer obtained by this invention has the potential to serve as a novel functional material, and the waste residue is effectively reused, achieving environmental protection and energy conservation. The processing technology is simple, molding is rapid, the dosage is low, the treatment effect is good, the performance is stable, the mechanical properties are improved, and it also has good adsorption properties, resulting in significant economic and social benefits. Attached Figure Description
[0034] Figure 1 The image shows the XRD pattern of the 3D-printed carbon nanotube-reinforced inorganic polymer obtained in Example 1 of this invention. Detailed Implementation
[0035] This invention utilizes the advantages of 3D printing's layer-by-layer molding, the excellent rheological properties of inorganic polymer slurries, the two-dimensional structure of carbon nanotubes, and the use of foaming agents to increase the specific surface area of materials. By selecting appropriate contents of slag, fly ash, metakaolin, or coal gangue, carbon nanotubes are introduced into an alkaline-activated solution. Under the action of ultrasound, the van der Waals bonds of the carbon nanotubes are opened to achieve solid solution. During the stirring process, the slurry is cooled in a water bath to extend the time available for printing. H2O2 is added as a foaming agent to achieve porosity of the material. CMC (sodium carboxymethyl cellulose) is added to adjust the viscosity of the slurry to make it suitable for 3D printing direct writing molding.
[0036] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0037] Example 1
[0038] The preparation process of Example 1 was carried out according to the following steps:
[0039] (1) Preparation of alkaline activated silicate solution: Alkaline activated solution is prepared by mixing potassium silicate solution and solid potassium hydroxide at a molar ratio of SiO2:KOH of (0.8-1):1 and stirring with a magnetic stirrer for 30 min.
[0040] (2) Pretreatment of inorganic polymer powder mixing: Coal gangue and fly ash powder were mechanically crushed and ground to a particle size of about 5μm, dried in an oven at 60℃, and sieved through a 100-mesh sieve. Coal gangue and slag were mechanically mixed for 5 minutes according to a certain mass ratio of 1:1 (75g of coal gangue and 75g of fly ash were added this time).
[0041] (3) Preparation of alkaline activation solution containing carbon nanotubes: Carbon nanotubes are slowly added to the alkaline activation silicate solution prepared in step (1). The mass ratio of carbon nanotubes to alkaline activation silicate solution is 21.2%. An alkaline activation solution containing carbon nanotubes is obtained. The solution is ultrasonically dispersed for 15 minutes to obtain a well dispersed alkaline activation solution containing carbon nanotubes.
[0042] (4) Preparation of carbon nanotube / inorganic polymer slurry: Add the inorganic polymer powder obtained in step (2) to the alkaline activation solution containing carbon nanotubes obtained after ultrasonication in step (3), wherein the mass ratio of inorganic polymer powder to alkaline activation solution containing carbon nanotubes obtained in step (3) is 150:94, and add a certain amount of deionized water to adjust the viscosity of inorganic polymer slurry, wherein the mass ratio of deionized water to alkaline activation solution containing carbon nanotubes is 1:8. Under the condition of water bath cooling, mechanically stir with an electric stirrer for 20 minutes to obtain a relatively viscous carbon nanotube / inorganic polymer slurry.
[0043] (5) Cooling and mechanical stirring: Place the beaker containing carbon nanotube / inorganic polymer slurry in 21°C cool water and stir the carbon nanotube / inorganic polymer slurry in the beaker for 20 minutes using an electric stirrer.
[0044] (6) Preparation of foamed printing paste: 3g of H2O2 as foaming agent and 5g of CMC as thickener are added to the carbon nanotube / inorganic polymer paste obtained in step (5), and the mixture is stirred for 5 minutes using a mechanical stirrer.
[0045] (7) Printing slurry filling and printing: Transfer the foamed printing slurry into the printing cylinder in one go. Use a large centrifuge or vibrator to make the slurry in the cylinder sink completely to the bottom of the cylinder and centrifuge for 5 minutes. 3D printing process of composite slurry: Under room temperature conditions, fix the cylinder to the ceramic 3D printer, use a 1mm direct-write forming printing needle, extrusion ratio of 0.9, extrusion linewidth of 1mm, leakage return distance of 1.0mm, return speed of 1800mm / s, first layer height of 90% of the set layer height, first layer extrusion linewidth of 100%, first layer printing deceleration ratio of 0.3, set layer height of 1.0mm, fill rate of 25%, shell and fill overlap rate of 10%, fill extrusion linewidth of 100%, minimum fill length of 1mm, and fill once for each printed layer. Use an air pump as the printing propulsion device and adjust the air pressure to 0.22MPa. Run the preset printing program, print the cube model, and start printing;
[0046] (8) Curing process of carbon nanotube reinforced inorganic polymer: The 3D printed carbon nanotube reinforced inorganic polymer obtained in step (7) is placed in an oven at 60°C and dried for 1 day.
[0047] The carbon nanotube-reinforced inorganic polymer obtained after step (8) of Example 1 is a hollow cube with a side length of 35 mm. It consists of 30 layers of slurry stacked in a regular manner, with a clear outline. The mechanical properties of the sample obtained after step (8) of Example 1 were tested on an electronic universal testing machine. The compressive strength of the sample was 9.5 MPa, which shows that it has certain mechanical properties. Figure 1 This is the XRD diffraction pattern of the sample.
[0048] Example 2
[0049] The preparation process for Example 2 was carried out according to the following steps:
[0050] (1) Preparation of alkaline activated silicate solution: Alkaline activated solution is prepared by mixing potassium silicate solution and solid potassium hydroxide at a molar ratio of SiO2:KOH of 1:1 and stirring with a magnetic stirrer for 100 min.
[0051] (2) Pretreatment of inorganic polymer powder mixing: Kaolin was calcined in a muffle furnace at 800℃ for 2 hours to obtain metakaolin. The metakaolin and slag powder were mechanically crushed and ground to a particle size of about 5μm. They were then dried in an oven at 60℃ and sieved through a 100-mesh sieve. The metakaolin and slag were mechanically mixed at a certain mass ratio for 5 minutes, with the mass ratio of metakaolin to slag being 1:1.5 (50g of metakaolin and 75g of slag were added in this case).
[0052] (3) Preparation of alkaline activation solution containing carbon nanotubes: Carbon nanotubes are slowly added to the alkaline activation silicate solution prepared in step (1). The mass ratio of carbon nanotubes to alkaline activation silicate solution is 11.76%. Alkaline activation solution containing nanotubes is obtained. The solution is ultrasonically dispersed for 15 minutes to obtain a well dispersed alkaline activation solution containing carbon nanotubes.
[0053] (4) Preparation of carbon nanotube / inorganic slurry: Add the inorganic polymer powder obtained in step (2) to the carbon nanotube-containing alkaline activation solution obtained after ultrasonication in step (3), wherein the mass ratio of inorganic polymer powder to the carbon nanotube-containing alkaline activation solution obtained in step (3) is 125:95, and add a certain amount of deionized water to adjust the viscosity of inorganic polymer slurry, wherein the mass ratio of deionized water to carbon nanotube-containing alkaline activation solution is 1.5:8. Under the condition of water bath cooling, mechanically stir with an electric stirrer for 20 minutes to obtain a relatively viscous carbon nanotube / inorganic polymer slurry.
[0054] (5) Cooling and mechanical stirring: Place the beaker containing carbon nanotube / inorganic polymer slurry in water at 24°C and stir the slurry in the beaker for 18 minutes using an electric stirrer.
[0055] (6) Preparation of foamed printing paste: 2g of H2O2 as foaming agent and 5g of CMC as thickener are added to the carbon nanotube / inorganic polymer paste obtained in step (5), and the mixture is stirred for 5min using a mechanical stirrer.
[0056] (7) Printing slurry filling and printing: Transfer the foamed printing slurry into the printing cylinder in one go. Use a large centrifuge or vibrator to make the slurry in the cylinder sink completely to the bottom of the cylinder and centrifuge for 5 minutes. 3D printing process of composite slurry: Under room temperature conditions, fix the cylinder to the ceramic 3D printer, use a 1mm direct-write forming printing needle, extrusion ratio of 0.9, extrusion linewidth of 1mm, leakage return distance of 1.0mm, return speed of 1800mm / s, first layer height of 90% of the set layer height, first layer extrusion linewidth of 100%, first layer printing deceleration ratio of 0.3, set layer height of 1.0mm, fill rate of 20%, shell and fill overlap rate of 10%, fill extrusion linewidth of 100%, minimum fill length of 1mm, and fill once for each printed layer. Use an air pump as the printing propulsion device and adjust the air pressure to 0.24MPa. Run the preset printing program, print the cylindrical model, and start printing;
[0057] (8) Curing process of carbon nanotube reinforced inorganic polymer: The 3D printed carbon nanotube reinforced inorganic polymer obtained in step (7) is placed in an oven at 60°C and dried for 2 days.
[0058] The carbon nanotube-reinforced inorganic polymer obtained after step (8) in Example 2 has a hollow cylindrical structure with a radius of 45.5 mm, a height of 7 mm, and a weight of 12.25 g. It has 10 layers from bottom to top, with each layer tightly stacked together and having a regular shape. An adsorption experiment on the sample was conducted, in which the sample was placed in a 300 ml solution of Cu, a heavy metal with a concentration of 100 mg / L. 2+ In the solution, after shaking in a shaker at 30℃ and 90r / min for 10h, the remaining Cu solution was analyzed. 2+ ICP testing was performed to determine the concentration of Cu in the sample. 2+ The adsorption capacity was 2.109 mg / g, and the adsorption rate was 86.125%, indicating that the sample prepared by the method of this invention has good adsorption capacity for the heavy metal Cu. 2+ It has a strong adsorption effect.
[0059] Example 3
[0060] Example 3 is based on Example 2, except that the amount of H2O2 added in step six is changed to 7g, while the other steps and parameters are the same.
[0061] The obtained carbon nanotube-reinforced inorganic polymer still exhibits a hollow cylindrical structure with a radius of 45.8 mm, a height of 7.5 mm, and a weight of 10.6 g. It consists of 10 layers from bottom to top, with each layer tightly stacked and regularly shaped. Heavy metal adsorption experiments were conducted on the sample by placing it in a 300 ml solution of Cu (Cu) at a concentration of 100 mg / L. 2+ In the solution, after shaking in a shaker at 30℃ and 90r / min for 10h, the remaining Cu solution was analyzed.2+ ICP testing was performed to determine the concentration of Cu in the sample. 2+ The adsorption capacity was 2.72 mg / g, and the adsorption rate was 93.6%, which was significantly higher than that of Example 2, indicating that the H2O2 foaming method of the present invention effectively improves the adsorption performance of the material.
[0062] Example 4
[0063] The preparation process for Example 4 was carried out according to the following steps:
[0064] (1) Preparation of alkaline activated silicate solution: Alkaline activated solution is prepared by mixing potassium silicate solution and solid potassium hydroxide at a molar ratio of SiO2:KOH of (0.8-1):1 and stirring with a magnetic stirrer for 600 min.
[0065] (2) Pretreatment of inorganic polymer powder mixing: Coal gangue, slag and fly ash powders were mechanically crushed and ground to a particle size of about 5μm, dried in an oven at 60℃, and sieved through a 100-mesh sieve. Coal gangue, fly ash and slag were mechanically mixed for 5 minutes according to a certain mass ratio of 1:0.5:1 (60g of coal gangue, 30g of fly ash and 60g of slag were added in this case).
[0066] (3) Preparation of alkaline activation solution containing carbon nanotubes: Carbon nanotubes are slowly added to the alkaline activation silicate solution prepared in step (1), wherein the mass ratio of carbon nanotubes to alkaline activation silicate solution is 7%, and an alkaline activation solution containing nanotubes is obtained. The solution is ultrasonically dispersed for 15 min to obtain a well dispersed alkaline activation solution containing carbon nanotubes.
[0067] (4) Preparation of carbon nanotube / inorganic polymer slurry: Add the inorganic polymer powder obtained in step (2) to the carbon nanotube-containing alkaline activation solution obtained after ultrasonication in step (3), wherein the mass ratio of inorganic polymer powder to the carbon nanotube-containing alkaline activation solution obtained in step (3) is 150:91, and add a certain amount of deionized water to adjust the viscosity of inorganic polymer slurry, wherein the mass ratio of deionized water to the carbon nanotube-containing alkaline activation solution is 2:9. Under the condition of water bath cooling, mechanically stir with an electric stirrer for 20 minutes to obtain a relatively viscous carbon nanotube / inorganic polymer slurry.
[0068] (5) Cooling and mechanical stirring: Place the beaker containing carbon nanotube / inorganic polymer slurry in 0°C cool water and stir the carbon nanotube / inorganic polymer slurry in the beaker for 15 minutes using an electric stirrer.
[0069] (6) Preparation of foamed printing paste: 3g of H2O2 as foaming agent and 5g of CMC as thickener are added to the carbon nanotube / inorganic polymer paste obtained in step (5), and the mixture is stirred for 5 minutes using a mechanical stirrer.
[0070] (7) Printing slurry filling and printing: Transfer the foamed printing slurry into the printing cylinder in one go. Use a large centrifuge or vibrator to make the slurry in the cylinder sink completely to the bottom of the cylinder and centrifuge for 5 minutes. 3D printing process of composite slurry: Under room temperature conditions, fix the cylinder to the ceramic 3D printer, use a 1mm direct-write forming printing needle, extrusion ratio of 0.9, extrusion linewidth of 1mm, leakage return distance of 1.0mm, return speed of 1800mm / s, first layer height of 90% of the set layer height, first layer extrusion linewidth of 100%, first layer printing deceleration ratio of 0.3, set layer height of 1.0mm, fill rate of 30%, shell and fill overlap rate of 10%, fill extrusion linewidth of 100%, minimum fill length of 1mm, and fill once for each printed layer. Use an air pump as the printing propulsion device and adjust the air pressure to 0.22MPa. Run the preset printing program, print the cylindrical model, and start printing;
[0071] (8) Curing process of carbon nanotube reinforced inorganic polymer: The 3D printed carbon nanotube reinforced inorganic polymer obtained in step (7) is placed in an oven at 60°C and dried for 1 day.
[0072] The carbon nanotube-reinforced inorganic polymer obtained after step (8) in Example 4 is a hollow cylinder with a diameter of 46.5 mm and a height of 25.1 mm. It consists of 18 layers stacked from top to bottom, with a clear outline and regular shape. Its compressive strength reaches 7.9 MPa, and it has certain mechanical properties. It is also effective against heavy metal Cu. 2+ The adsorption rate is 86.2%, indicating that it has certain adsorption performance.
[0073] Example 5
[0074] The preparation process in this embodiment is carried out according to the following steps:
[0075] (1) Preparation of alkaline activated silicate solution: Alkaline activated solution is prepared by mixing potassium silicate solution and solid potassium hydroxide at a molar ratio of SiO2:KOH of (0.8-1):1 and stirring with a magnetic stirrer for 600 min.
[0076] (2) Pretreatment of inorganic polymer powder mixing: Coal gangue, fly ash, metakaolin and slag powder were mechanically crushed and ground to a particle size of about 5μm, dried in an oven at 60℃, and sieved through a 100-200 mesh sieve. The coal gangue, fly ash, metakaolin and slag were mixed in a mass ratio of 1:0.5:0.5:1 (25g of coal gangue, 25g of fly ash, 25g of metakaolin and 50g of slag were added in this case).
[0077] (3) Preparation of alkaline activation solution containing carbon nanotubes: Slowly add carbon nanotubes to the alkaline activation silicate solution prepared in step (1), wherein the mass ratio of carbon nanotubes to the mass ratio of alkaline activation silicate solution is 7%, and obtain an alkaline activation solution containing carbon nanotubes. The solution is ultrasonically dispersed for 15 min to obtain a well dispersed alkaline activation solution containing carbon nanotubes.
[0078] (4) Preparation of carbon nanotube / inorganic polymer slurry: Add the inorganic polymer powder obtained in step (2) to the carbon nanotube-containing alkaline activation solution obtained after ultrasonication in step (3), wherein the mass ratio of inorganic polymer powder to the carbon nanotube-containing alkaline activation solution obtained in step (3) is 150:91, and add a certain amount of deionized water to adjust the viscosity of the inorganic polymer slurry, wherein the mass ratio of deionized water to the carbon nanotube-containing alkaline activation solution is 1.5:9.1, and mechanically stir with an electric stirrer for 20 minutes under water bath cooling conditions to obtain a relatively viscous carbon nanotube / inorganic polymer slurry.
[0079] (5) Cooling and mechanical stirring: Place the beaker containing carbon nanotube / inorganic polymer slurry in 20°C cool water and stir the carbon nanotube / inorganic polymer slurry in the beaker for 20 minutes using an electric stirrer.
[0080] (6) Preparation of foamed printing paste: 2g of H2O2 as foaming agent and 20g of CMC as thickener are added to the carbon nanotube / inorganic polymer paste obtained in step (5), and the mixture is stirred for 5 minutes using a mechanical stirrer.
[0081] (7) Printing slurry filling and printing: Transfer the foamed printing slurry into the printing cylinder in one go. Use a large centrifuge or vibrator to make the slurry in the cylinder sink completely to the bottom of the cylinder and centrifuge for 5 minutes. 3D printing process of composite slurry: Under room temperature conditions, fix the cylinder to the ceramic 3D printer, use a 1mm direct-write forming printing needle, extrusion ratio of 0.9, extrusion linewidth of 1mm, material leakage retraction distance of 1.0mm, retraction speed of 1800mm / s, first layer height of 90% of the set layer height, first layer extrusion linewidth of 100%, first layer printing deceleration ratio of 0.3, set layer height of 1.0mm, infill rate of 20%, shell and infill overlap rate of 10%, infill extrusion linewidth of 100%, minimum infill length of 1mm, and print one infill per layer. Use an air pump as the printing propulsion device and adjust the air pressure to 0.3MPa. Run the preset printing program, print the cube model, and start printing;
[0082] (8) Curing process of carbon nanotube reinforced inorganic polymer: The 3D printed carbon nanotube reinforced inorganic polymer obtained in step (7) is placed in an oven at 60°C and dried for 1 day.
[0083] The carbon nanotube-reinforced inorganic polymer obtained after step (8) has a regular shape and distinct outline, generally resembling a cuboid with a length of 45.5 mm, a width of 45.7 mm, and a height of 27.6 mm. It consists of 20 stacked layers from top to bottom, achieving a compressive strength of 6.5 MPa and exhibiting certain mechanical properties. For heavy metal Cu... 2+ The adsorption rate is 87.1%, indicating that it has certain adsorption performance.
[0084] Example 6
[0085] The preparation process of Example 6 is based on Example 1, except that the waste residue in step 2 is replaced with 75g of fly ash and 75g of slag, and the other steps are the same as those in Example 1.
[0086] The carbon nanotube-reinforced inorganic polymer obtained after step (8) of Example 6 is a hollow cylinder with a diameter of 45.8 mm, consisting of 28 layers of slurry stacked sequentially and with a clear outline. The mechanical properties of the sample obtained after step (8) of Example 6 were tested on an electronic universal testing machine, and the compressive strength of the sample was found to be 8.4 MPa, indicating certain mechanical properties. Regarding the heavy metal Cu... 2+ The adsorption rate is 83.2%, indicating that it has certain adsorption performance.
[0087] Based on the above examples, it can be seen that this method can successfully prepare a 3D-printed carbon nanotube-reinforced waste residue-based inorganic polymer, which also has strong mechanical and adsorption properties.
Claims
1. A method for preparing 3D-printed carbon nanotube-reinforced waste-based inorganic polymers, characterized in that, Includes the following steps: Step 1: Preparation of alkaline activated silicate solution: Mix potassium silicate solution with solid potassium hydroxide, with a SiO2:KOH molar ratio of (0.8-1):
1. Stir the mixed solution for 20-600 minutes to obtain alkaline activated silicate solution. The potassium silicate solution has a modulus of 3.1, n(SiO2) / n(K2O) = 3.1, and SiO2 accounts for 40% of the mass fraction of the potassium silicate solution. Step 2: Pre-treatment of inorganic polymer powder mixing: The waste residue consists of two or more of the following: slag, fly ash, metakaolin, and coal gangue; the waste residue is ground separately by mechanical crushing, and the ground waste residue powder is dried and sieved; the sieved waste residue is mechanically mixed according to a certain mass ratio to obtain inorganic polymer powder. The main components of the coal gangue are: 50-65 wt% SiO2 and 20-30 wt% Al2O3; the main components of the slag are: 25-35 wt% SiO2, 10-20 wt% Al2O3, and 40-50 wt% CaO; the main components of the fly ash are: 45-55 wt% SiO2, 30-40 wt% Al2O3, 5-10 wt% Fe2O3, and 2-5 wt% CaO; and the main components of the metakaolin are: 48-58 wt% SiO2 and 40-50 wt% Al2O3. When two types of waste residues are selected as raw materials, the mass ratio of coal gangue to slag is 1:(0.4-1.2), the mass ratio of coal gangue to fly ash is 1:(0.5-1), the mass ratio of coal gangue to metakaolin is 1:(0.4-0.8), the mass ratio of fly ash to slag is 1:(0.4-1.2), the mass ratio of metakaolin to slag is 1:(0.5-1.8), the mass ratio of metakaolin to fly ash is 1:(0.8-1.5), and the mass ratio of the total mass of inorganic polymer powder to the mass ratio of alkali-activated silicate solution is (1.25-2.5):
1. When three types of waste residues are selected as raw materials, the mass ratio of coal gangue:fly ash:slag is 1:(0.5-1):(0.4-1.2), the mass ratio of coal gangue:fly ash:metakaolin is 1:(0.5-1):(0.4-1.2), the mass ratio of coal gangue:fly ash:metakaolin is 1:(0.8-1.5), and the mass ratio of metakaolin to fly ash is (1.25-2.5):
1. The mass ratio of kaolin is 1:(0.5-1):(0.4-0.8), the mass ratio of fly ash:meta-kaolin:slag is (0.5-1):(0.4-0.8):(0.4-1.2), the mass ratio of coal gangue:meta-kaolin:slag is 1:(0.4-0.8):(0.4-1.2), and the mass ratio of the total mass of inorganic polymer powder to the mass of alkali-activated silicate solution is (1.25-2.5):1; when four types of waste residues are selected as raw materials, the mass ratio of coal gangue:fly ash:meta-kaolin:slag is 1:(0.5-1):(0.4-0.8):(0.4-1.2), and the mass ratio of the total mass of inorganic polymer powder to the mass of alkali-activated silicate solution is (1.25-2.5):1; Step 3: Preparation of alkaline activation solution containing carbon nanotubes: Add carbon nanotubes to the alkaline activation silicate solution, with the mass of carbon nanotubes accounting for 6%-25% of the mass of the alkaline activation silicate solution; obtain an alkaline activation solution containing carbon nanotubes; after ultrasonic dispersion treatment, obtain a well dispersed alkaline activation solution containing carbon nanotubes. Step 4: Preparation of carbon nanotube / inorganic polymer slurry: Add inorganic polymer powder to the carbon nanotube-containing alkaline activation solution, with a mass ratio of inorganic polymer powder to carbon nanotube-containing alkaline activation solution of (120-180):(75-95). Then add deionized water to adjust the viscosity to obtain the carbon nanotube / inorganic polymer slurry; wherein the mass ratio of deionized water to carbon nanotube-containing alkaline activation solution is (1-2):(7.5-9.5). Step 5: Cooling and mechanical stirring: Cool the container containing the carbon nanotube / inorganic polymer slurry to 0-24℃ and stir the carbon nanotube / inorganic polymer slurry for 15-60 minutes to obtain the carbon nanotube / inorganic polymer composite slurry. Step 6: Preparation of foamed printing paste: Add foaming agent H2O2 and thickener CMC to carbon nanotube / inorganic polymer composite paste in sequence. The mass ratio of H2O2 to inorganic polymer powder in step 4 is (2-8):100, and the mass ratio of CMC to inorganic polymer powder in step 4 is (1-25):
100. Stir for 3-10 minutes to obtain foamed printing paste. Step 7, Printing Slurry Filling and Printing: Transfer the foamed printing slurry into the printing barrel, ensuring the slurry completely sinks to the bottom for printing, resulting in 3D-printed carbon nanotube-reinforced inorganic polymer. The printing process is as follows: At room temperature, fix the printing barrel onto the ceramic 3D printer. The direct-write printing nozzle length is 0.5mm-10mm, the extrusion ratio is 0.5-0.9, the extrusion linewidth is 0.5mm-10mm, and the material leakage retraction distance is 0.5mm-1.0mm. mm, pullback speed 800mm / s-1800mm / s, set layer height 0.5mm-1.0mm, first layer height 50%-90% of set layer height, first layer extrusion line width 100%, first layer printing deceleration ratio 0.3-0.5, fill rate 20-50%, print shell and fill overlap rate 10%-20%, fill extrusion line width 80%-100%, minimum fill length 1mm-5mm, fill once per layer printed; pneumatic printing adjusts air pressure to 0.05-0.8MPa; Step 8: Curing of carbon nanotube-reinforced inorganic polymer: Place the obtained 3D-printed carbon nanotube-reinforced inorganic polymer in an oven at 25-80℃ and dry for 0.5-3 days to obtain the final product of 3D-printed carbon nanotube-reinforced inorganic polymer.
2. The method for preparing 3D-printed carbon nanotube-reinforced waste-based inorganic polymers according to claim 1, characterized in that, In step four, the mass ratio of carbon nanotubes to inorganic polymer powder is (5-20):100; the mass ratio of deionized water to carbon nanotube-containing alkaline activation solution is (1-2):(8-8.5).
3. The method for preparing 3D-printed carbon nanotube-reinforced waste-based inorganic polymers according to claim 2, characterized in that, In step five, the container containing the carbon nanotube / inorganic polymer slurry is cooled in an environment of 20℃-22℃.
4. The method for preparing 3D-printed carbon nanotube-reinforced waste-based inorganic polymers according to claim 3, characterized in that, In step six, the mass ratio of H2O2 to inorganic polymer powder in step four is (2-3):100, and the mass ratio of CMC to inorganic polymer powder is (4-8):100.
Citation Information
Patent Citations
All-solid waste fiber reinforced geopolymer composite material suitable for 3D printing technology
CN113754359A
Preparation method of biochar-based hierarchical pore monolithic adsorbent
CN115999515A
Preparation method of carbonized 3D printing foam concrete
CN116177959A
Light carbon nanotube reinforced aluminosilicate polymer foam material and preparation method thereof
CN111153676A